Observation of TAE mode driven by off-axis ECRH induced barely trapped energetic electrons in EAST tokamak. (12th March 2021) - Chu, N.; Sun, Y.; Shen, B.; Hu, Y.J.; Gu, S.; Jia, M.; Wang, H.H.; Shi, T.H.; Bao, J.; Duan, Y.M.; He, K.Y.; Li, E.; et al.
Abstract: A toroidal Alfvén eigenmode (TAE) is excited by electron cyclotron resonance heating (ECRH) induced barely trapped energetic electrons in experimental advanced superconducting tokamak . This TAE appears in the low density EAST discharges under pure off-axis ECRH heating. After analysing the ECRH power modulation induced local density and temperature oscillations, the location of this TAE mode and the power deposition of ECRH are determined. This edge localized TAE mode drifts in ion-diamagnetic direction may be driven by barely trapped energetic electrons considering the contribution of poloidal bounce effect in the general wave-particle resonance condition. The experimental observations also demonstrate that ECRH power modulation with fixed frequency could be used as an effective diagnostic tool to study the internal properties of MHD modes as well as particle and heat transports.